Familial Mediterranean fever: current perspectives - Sönmez HE (Dove Medical Press, 2016)
Hafize Emine Sönmez,* Ezgi Deniz Batu,* Seza ÖzenDepartment of Pediatrics, Division of Rheumatology, Hacettepe University Faculty of Medicine, Ankara, Turkey *These authors contributed equally to this workAbstract: Familial Mediterranean fever (FMF) is the most frequent monogenic autoinflammatory disease, and it is characterized by recurrent attacks of fever and polyserositis. The disease is associated with mutations in the MEFV gene encoding pyrin, which causes exaggerated inflammatory response through uncontrolled production of interleukin 1. The major long-term complication of FMF is amyloidosis. Colchicine remains the principle therapy, and the aim of treatment is to prevent acute attacks and the consequences of chronic inflammation. With the evolution in the concepts about the etiopathogenesis and genetics of the disease, we have understood that FMF is more complicated than an ordinary autosomal recessive monogenic disorder. Recently, recommendation sets have been generated for interpretation of genetic testing and genetic diagnosis of FMF. Here, we have reviewed the current perspectives in FMF in light of recent recommendations.Keywords: familial Meditarranean fever, recommendation, child